Modelling and characterisation of heterostructure devices for MMIC application - Subrata Halder. (2008)
For development of MMIC amplifier using GaAs HEMT and HBT devices developed in-house, it is essential to select devices of appropriate size for best power performance. The overall objective of this has been dc and microwave characterization of HEMT and HBT devices.